(untitled) (Bangladesh Journal of Botany, 2022)
Karyotypes parameters in four selected Turkish bean genotypes (BT, HK, VN, and EL) were studied. Genotypes (4 levels) and chromosomes (11 levels) were compared in factorial experiment based on completely randomized design with five replications. Genotypes showed significant differences in long arm, short arm and total chromosome length and divided into three separate groups. Genotypes BL and HK were placed together in a separate group, probably showing the weaker kinship with the other genotypes. Also, the significant differences in all recorded parameters were observed among chromosomes of each genotype. All genotypes were diploid 2n = 22 with no satellite and differed significantly in karyotypic parameters. The most and the least chromatin length (34.24 μm and 15.65 μm) were observed in BT and EL genotypes, respectively. Also, all genotypes showed high chromosomal symmetry and categorized in Stebbins’s Class 1A. The karyotype of genotype BT was found to be more symmetrical than others. Bangladesh J. Bot. 51(2): 281-288, 2022 (June)